2018
DOI: 10.21003/ea.v167-03
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the level of penetration of import dependence in the context of the import substitution policy in Ukraine

Abstract: Abstract. Introduction. A situation when factors that stimulate an increase in the volume of imports have a growing impact and barrier and compensatory countermeasures are not formed is typical of the current stage of development of the Ukrainian economy. When solving this problem in the context of the import substitution policy in Ukraine, it is necessary to assess the level of import penetration into the domestic market and to find out the dependence of the national economy on its scale. The purpose is to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 6 publications
0
6
0
2
Order By: Relevance
“…Given its high integration, it is worth focusing on specific areas of development, in particular on the field of plant protection agents. The relevance of such a line of research is confirmed both by natural aspects (the share of agricultural land in the total land fund of Ukraine is more than 70.0%), and market-political aspects (in Ukraine, political processes of the land market formation are actively ongoing, and hence the development of farms is predicted, but their functioning is impossible without plant protection agents) (Panukhnyk et al, 2019;Vasyltsiv et al, 2017).…”
Section: (5)mentioning
confidence: 99%
“…Given its high integration, it is worth focusing on specific areas of development, in particular on the field of plant protection agents. The relevance of such a line of research is confirmed both by natural aspects (the share of agricultural land in the total land fund of Ukraine is more than 70.0%), and market-political aspects (in Ukraine, political processes of the land market formation are actively ongoing, and hence the development of farms is predicted, but their functioning is impossible without plant protection agents) (Panukhnyk et al, 2019;Vasyltsiv et al, 2017).…”
Section: (5)mentioning
confidence: 99%
“…The most rational way out of this situation, scientists see more in increasing investment and innovation activity of the business in the direction of capital investment implementation. However, according to the authors Ilyash et al (2020), Vasyltsiv et al (2017) the lack of institutional elements of innovation infrastructure and investment potential of the economy hinder the growth of investment attractiveness of enterprises, and, consequently, their innovative development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The level of competition in the internal market is also influenced by the quality of the state policy with regard to economic protectionism. Just regarding the domestic market of motor transport passenger transportation in Ukraine, there is no competition from foreign motor transport companies [3] and this should be considered in two ways. On the one hand, it creates better conditions for the enterprise functioning and development in this field.…”
Section: Literature Reviewmentioning
confidence: 99%